Overview on CO2 Valorization: Challenge of Molten Carbonates - Chery, Déborah; Lair, Virginie; Cassir, Michel (Frontiers in Energy Research, 2015)
The capture and utilisation of CO2 is becoming progressively one of the significant challenges in the field of energetic resources. Whatever the energetic device, it is impossible to avoid completely the production of greenhouse gas, even parting from renewable energies. Transforming CO2 in a valuable fuel, such as alcohols, CO or even C, could constitute a conceptual revolution in the energetic bouquet offering a huge application domain. Although several routes have been tested for this purpose, on which a general panorama will be given here, molten carbonates are attracting a renewed interest aiming at dissolving and reducing carbon dioxide in such melts. Because of their unique properties, molten carbonates are already used as electrolytes in molten carbonate fuel cells; they can also provoke a breakthrough in a new economy considering CO2 as an energetic source rather than a waste. Molten carbonates science and technology is becoming a strategic field of research for energy and environmental issues. Our aim in this review is to put in evidence the benefits of molten carbonates to valorise CO2 and to show that it is one of the most interesting routes for such application.